Data-driven outreach to opportunity youth using population data and Geographic Information System technology. (May 2021) - Wang, Chuyuan; Mody, Elizabeth H; Hunting, Dan; Hoyt, James; Ferguson, Kristin M
Summary: Opportunity youth (i.e. ages 16–24 who are neither working nor in school) are difficult to engage in services. Population-level data and Geographic Information System (GIS) technology play a critical role in helping social work practitioners understand where target populations reside and which characteristics are most salient to their service needs. This case study of the Opportunities for Youth Coalition demonstrates the use of population-level data and GIS technology in social work research and practice. We describe the collective impact approach, extant methods of youth outreach, and the Coalition's efforts to address youth disconnection. We used American Community Survey data, ArcGIS software, and hot spot analysis to answer three research questions. Findings: In the Phoenix Metro Area, there are 75, 200 opportunity youth. Greater percentages of youth of color are opportunity youth in comparison with White youth. One in three individuals who have limited English proficiency and who have a disability are opportunity youth. Nearly one in five individuals living in poverty is an opportunity youth. We identify the top five high population density areas for opportunity youth. Further, we highlight three ways that the Coalition's use of data and GIS technology has enhanced youths' and service providers' engagement: (1) increased referrals, (2) increased involvement of organizations, and (3) increased understanding of special populations. Applications: We discuss the benefits and challenges of using population data and GIS technology to guide youth engagement. We conclude with strategies for community practitioners to replicate in other geographic areas and with other hard-to-reach populations.